Cardiopulmonary response to oxygen therapy in hypoxaemic chronic airflow obstruction. Issue 11 (November 1989) - Hunt, J M; Copland, J; McDonald, C F; Barter, C E; Rochford, P D; Pierce, R J
Abstract : The acute change in pulmonary artery pressure in response to oxygen may have prognostic value for patients with chronic obstructive pulmonary disease treated with long term domiciliary oxygen. A study was carried out to elucidate the mechanism of the acute cardio-respiratory response to oxygen in such patients and to determine whether it can be quantified non-invasively. The effects of acute oxygen administration (100% for 20 minutes and 28% oxygen for 24 hours) were assessed by non-invasive means and right heart catheterisation in 17 patients with severe stable hypoxaemic chronic obstructive pulmonary disease. Measurements included change in the ratio of dead space to tidal volume (VD/VT), effective pulmonary capillary blood flow (by rebreathing and single breath soluble gas uptake: QRB, QSB), left ventricular ejection fraction (radionuclide ventriculography), and M mode echocardiographic estimates of ventricular diameters and fractional shortening. These values were compared with those obtained from right heart catheter measurements of pulmonary artery pressure, cardiac index (thermodilution and direct carbon dioxide Fick: QTD, QFICK), and pulmonary vascular resistance. Oxygen administration resulted in a significant fall in pulmonary artery pressure, QTD, and QRB and a significant increase in VD/VT. The fall in QRB after 100% oxygen breathing for 20 minutes correlated strongly with the fall in pulmonary artery pressure (r = 0.86). There was no correlation between the fall in pulmonary artery pressure and the fall in QSB or the risen in VD/VT. Left ventricular ejection fraction did not change significantly. Echocardiography was technically unsatisfactory because of lung hyperinflation. Apart from a possible relation between VO2max and fall in pulmonary artery pressure after 24 hours of 28% oxygen breathing (r = 0.49, p less than 0.1) none of the baseline respiratory function measurements predicted the fall in pulmonary artery pressure or QRB. It is concluded that the cardiopulmonary response to acute oxygen breathing in patients with hypoxic chronic obstructive pulmonary disease includes a reduction in pulmonary artery pressure and cardiac output and a redistribution of pulmonary blood flow, and that rebreathing measurements of effective pulmonary blood flow can be used to quantify this response non-invasively.